THE STATE AND THE HOLY QURAN: POLITICS OF THE QURAN TRANSLATION BY THE MINISTRY OF RELIGIOUS AFFAIRS - Dede Rodin; Rosihon Anwar; Dody S Truna; Wahyudin Darmalaksana (Himpunan Peminat Ilmu-Ilmu Ushuluddin (HIPIUS), 2021)
Quran Translation by the Ministry of Religious Affairs entitled “Al-Qur’an dan Terjemahannya” which has been improved and refined for the third time shows the involvement of the state in providing Quran translation for Muslims. This article aims to show how politics and state policies in the translation of Quran in Indonesia as the power-knowledge, and how this power-knowledge is related to other power-knowledge. By analyzing all edition of “Al-Qur’an dan Terjemahannya” published by the Ministry of Religious Affairs as well as a set of interviews, this article concluded that Quran translation by the Ministry of Religious Affairs is an authoritative strategy of the state in accommodating Muslims interest to comprehend their holy Quran. At the same time, through this translation, the interest of the state in maintaining its stability of power is accommodated as well. The state power-knowledge in the form of Quran translation by the Ministry of Religious Affairs is not only focused on the state (The Ministry of Religious Affairs), but also related to other translation of Quran as the power-knowledge in the society.